Core nucleus polarization in lambda (^) hypernuclei - Zaliman Sauli (School of Microelectronic Engineering, 2012)
The main objective is develop an extended Thomas-Fermi theory using a local density approach ("Thomas Fermi" model for short) to calculate binding energies, root mean square radii, density distributions for nuclei and hypernuclei and demonstrate that for "realistic" L-nuclear interactions, the core polarization effects are in general very small, both the polarizing energies as well as the change in rms radii.